Pengalaman penjagaan ibu bapa tua oleh anak dewasa: satu kajian dalam kalangan penduduk melayu bandar berpendapatan rendah. - Khadijah Alavi; Rahim M. Sail; Khairuddin Idris; Asnarulkhadi Abu Samah (Universiti Kebangsaan Malaysia, 2010)
The main purpose of this article is to understand from the Islamic perspective the nature of adult children caregivers’ experiences towards their aged parents and how they manage their daily activities while caring for their own family as well as manage their career. Phenomenology was chosen as the approach in this study. Informants were Malay adult children caring for their elderly parents aged 60 years and above, and from low income families in Kuala Lumpur. The findings encompass two major experiences of the adult children, which include their experiences before (pre experience) and while (actual experience) caring for the elderly parents. In going through these caregiving experiences, the informant assume the responsibility of caring (out of gratitude, dedication, sense of commitment, reciprocity and sharing problems); logical knowledge (based on reflection of one’s past deeds); and for tangible support (financial assistance and parents’ relationship with their daughters) and non- tangible support (such as cleaning the house, cooking and protecting their elderly parents’ feelings). This article conclude that an adult child who wants to take care of the aged parents must start with a feeling of ‘tawakal’ (taking into account individual strength and ability before committing to caregiving) and ends with being resolute, patient and acceptance in facing the challenges and problems in caring for their aged parents.